Conocimiento tributario en los estudiantes del cuarto - quinto nivel de la facultad de ciencias económicas y de negocios de la Universidad Nacional de la Amazonía Peruana - 2021 - Torres Sinarahua, Magno Gabriel (2023)
The research consisted of analyzing the tax knowledge in the students of the fourth - fifth level of the Faculty of Economic and Business Sciences of the National University of the Peruvian Amazon - 2021. The study was of the observational, descriptive, cross-sectional and retrospective type since It will be a non-experimental study, the population was made up of 278 students whose sample was 162 students from the Faculty of Economic and Business Sciences of the National University of the Peruvian Amazon, having used the survey as a data collection technique, and as an instrument It was the quiz. The information was processed in a computerized way, for which the computational statistical package SPSS version 23 in Spanish and the Microsoft Excel spreadsheet software were extracted, the results were classified for the elaboration of tables and their representation in graphs. The analysis and interpretation of the information was used using the descriptive analysis (Frequency, average ( ), percentage (%), the research hypothesis was lent: The students of the fourth - fifth level of the Faculty of Economic and Business Sciences of The National University of the Peruvian Amazon has a high level of tax knowledge.